The territory as a Cultural construction: between realities and meanings (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
This research proposes to interpret the different theoretical conceptions about development that have been raised throughout the discussions on the territory. For the accomplishment of this work it was necessary, an exhaustive review of the literature, so that it has a documentary character, accompanied with some empirical observations in some rural contexts of Nicaragua. Territory is no more than a social and cultural construction, each space is produced and reproduced from its own dynamics driven by historical, political, economic and cultural processes, each one is built on two dimensions: reality and need. It should be noted that each territory is dynamic and therefore constantly mutating, indicating that its meanings also undergo a constant variation. Each individual and every social organization generates a space, builds a territory, and also promotes transformation processes in them. It is in the territory where a culture is built, a way of life, a worldview, where a set of social institutions are configured and dialectically reconfigured.
Keywords: Territory; space; culture; rural development; community